Vitamin D in the diet and their effect on the nervous system - Koprivica, Marko M; Bjelanović, Jelena (Medicinski časopis, 2023)
Vitamin D is a liposoluble organic compound that, in addition to calcium metabolism and its effect on the skeletal system, also has numerous other effects on other organ systems, such as the cardiovascular, endocrine, skeletal and immune, but also on the central nervous system. The primary source of vitamin D is food of animal origin; however, vitamin D is synthesized in the skin upon its exposure to sunlight. In this paper, we will also present the studies corroborating the theory that numerous neurological and psychiatric manifestations are due to deficiency of vitamin D.